2005
DOI: 10.1097/01.alc.0000179382.64752.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress on the Voluntary Intake of a Sweetened Ethanol Solution in Pair-Housed Adolescent and Adult Rats

Abstract: Previous reports of heightened voluntary ethanol intake among adolescent rats are not a function of isolate stress but are evident in pair-housed animals. Adolescents were more sensitive to ethanol/stress interactions than were adults, with the elevated ethanol intake of pair-housed adolescents selectively disrupted by chronic stress, a stress-induced disruption not evident in adults. Likewise, ethanol disrupted behavioral adaptation to the footshock stressor among adolescents but not adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
98
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 46 publications
10
98
2
1
Order By: Relevance
“…To the extent that some of these consequences of ethanol use serve as feedback cues to limit the amount consumed during a drinking session, the reduced sensitivity of adolescents to these ethanol effects may serve as permissive factors allowing greater ethanol intake among adolescents. The results from our laboratory have indeed shown that adolescent animals voluntarily drink more ethanol than the adults under a variety of experimental situations (e.g., Brunell and Spear 2005;Doremus et al 2005). High ethanol consumption is also evident among human adolescents, as shown by the widespread occurrence of binge drinking in this population (e.g., see "Monitoring the future" survey data summarized in Johnston et al 2002).…”
Section: Introductionmentioning
confidence: 66%
“…To the extent that some of these consequences of ethanol use serve as feedback cues to limit the amount consumed during a drinking session, the reduced sensitivity of adolescents to these ethanol effects may serve as permissive factors allowing greater ethanol intake among adolescents. The results from our laboratory have indeed shown that adolescent animals voluntarily drink more ethanol than the adults under a variety of experimental situations (e.g., Brunell and Spear 2005;Doremus et al 2005). High ethanol consumption is also evident among human adolescents, as shown by the widespread occurrence of binge drinking in this population (e.g., see "Monitoring the future" survey data summarized in Johnston et al 2002).…”
Section: Introductionmentioning
confidence: 66%
“…Although ethanol consumption levels reached early in adolescence (7.5 g/kg/d) approached those seen in P rats (Files et al, 1992), blood ethanol concentrations were not assessed in this study due to difficulties in pin-pointing the specific timing of drinking bouts that are interspersed throughout the dark cycle (and episodically continued through the light cycle as well) in both adolescent and adult Sprague-Dawley rats (see Brunell and Spear, 2005). Given the episodic nature of home cage consumption (e.g., Brunell and Spear, 2005), it is possible that ethanol burdens at any point in time were not sufficiently high to exert a lasting influence on subsequent intake.…”
Section: Discussionmentioning
confidence: 99%
“…Given the episodic nature of home cage consumption (e.g., Brunell and Spear, 2005), it is possible that ethanol burdens at any point in time were not sufficiently high to exert a lasting influence on subsequent intake. That is, despite the overall high daily ethanol intakes of the adolescents, their blood ethanol concentrations may not have reached pharmacologically significant levels or levels sufficient to induce tolerance, and hence, may not have affected intake in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Variables that have been previously investigated in adolescent self-administration paradigms include sex, age, ethanol fluid concentration, isolate-housing and use of different sipper-tube types; however, these studies provided 24-hour access to the ethanol solutions (Bell et al, 2006;Brunell and Spear, 2005;Doremus et al, 2005;Ehlers et al, 2007;Fullgrabe et al, 2007;Lancaster et al, 1996;Siciliano and Smith, 2001). In the present experiment, male and female adolescent and adult rats were compared for ethanol self-administration behavior during one hour limited-access sessions, which have been proposed to model binge-like behavior (Martinetti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%